Social values depicted in the Aklat Adarna's International Edition series a content analysis - Soriano, Ma. Bettina T.; Buenrostro, Juan Jr. C. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1997)
This is intended to examine the worth of Aklat Adarna's International Edition series as a potential tool for teaching social values to children. To determine the social values depicted in Aklat Adarna's International Edition, a content analysis was conducted by first giving brief descriptions of each story based on the literary components of theme, plot, character, and setting and then by giving each story a qualitative evaluation based on the identification and tabulation of the social values it depicts.
The results of this content analysis reveal that: 1) the themes of the stories embody moral lessons, the plots are simple, the characters are interesting, and the settings are appropriate; and 2) only two of the stories scored high in the depiction of social values, one story failed to depict any of the social values, and the eighteen other stories scored low or none at all in the depiction of social values.
In conclusion, only two stories among the Aklat Adarna's International Edition are worthy of selection, acquisition, and recommendation. It was recommended that for entertainment purposes, the school librarian may select and acquire the entire series for the library's collection and recommend it for children's leisurely reading, and the school librarian in search of materials rich in the depiction of social values should examine other locally-published children's books series.
Undergraduate thesis (B.L.S.)--University of the Philippines, Diliman
Vita.
Computer printout.
Thesis (Bachelor of Library Science)
Keywords: Illustrated books, Children's -- History and criticism. -- Philippines; Social values in literature